Comparative analysis of cyanobacterial communities in gypsum outcrops: insights from sites in Israel and Poland - Němečková, Kateřina; Mareš, Jan; Košek, Filip; Culka, Adam; Dudák, Jan; Tymlová, Veronika; Žemlička, Jan; Jehlička, Jan (Extremophiles, 2024)
Today, the biodiversity of endolithic microbial colonisations are only partly understood. In this study, we used a combination of molecular community metabarcoding using the 16S rRNA gene, light microscopy, CT-scan analysis, and Raman spectroscopy to describe gypsum endolithic communities in 2 sites-southern Poland and northern Israel. The obtained results have shown that despite different geographical areas, climatic conditions, and also physical features of colonized gypsum outcrops, both of these sites have remarkably similar microbial and pigment compositions. Cyanobacteria dominate both of the gypsum habitats, followed by Chloroflexi and Pseudomonadota. Among cyanobacteria, Thermosynechococcaceae were more abundant in Israel while Chroococcidiopsidaceae in Poland. Interestingly, no Gloeobacteraceae sequences have been found in Poland, only in Israel. Some of the obtained 16S rRNA gene sequences of cyanobacteria matched previously detected sequences from endolithic communities in various substrates and geographical regions, supporting the hypothesis of global metacommunity, but more data are still needed. Using Raman spectroscopy, cyanobacterial UV-screening pigments-scytonemin and gloeocapsin have been detected alongside carotenoids, chlorophyll a and melanin. These pigments can serve as potential biomarkers for basic taxonomic identification of cyanobacteria. Overall, this study provides more insight into the diversity of cyanobacterial endolithic colonisations in gypsum across different areas.
Keywords: Phototrophs; Cyanobacteria; RNA, Ribosomal, 16S; Israel; síran vápenatý; 16S rRNA; mikrobiota; Calcium Sulfate; Endoliths; Izrael; sinice; Poland; Microbiota; RNA ribozomální 16S; Metacommunity; Gypsum; Polsko